Aerodynamic characteristic assessment of an airfoil using open circuit wind tunnel and computational fluid dynamics - Khan, Tabrej (2015)
This work is an attempt to investigate the airflow characteristics around an airfoil by using the existing wind tunnel of the University Putra Malaysia (UPM) and Computational Fluid Dynamics (CFD) methods. These results are compared to the available trusted experimental result of the University of Illinois at Urbana- Champaign UIUC (UIUC wind tunnel) for validity and assessment. A Clark Y airfoil was available at the laboratory and used therefore as the airfoil to be investigated. This airfoil was subjected to tests in the low-speed, open-circuit wind tunnel at different test-section velocities (7 m/s – 14 m/s). In order to be able to verify the investigation, the same airfoil definition with the same flow conditions as used in the wind tunnel test was also used for CFD’s calculation by using the PHOENICS software, which was available as supplementary joint work elaborated in a companion thesis work as listed in the references. The results of the above two methods were compared and analyzed. The data obtained were further verified by comparing it to the standard data of the UIUC wind tunnel, yielding to an impression that the UPM wind tunnel test results and CFD data exhibited considerable differences. However, both methods shared characteristics that are almost similar to UIUC wind tunnel. Further, the CFD data were found to have more similarity with the UIUC wind tunnel data if compared to those of the UPM wind tunnel data. Some differences that are exhibited by the wind tunnel results are assessed in view of uncertainties and accuracy. Overall, a systematic procedure has been followed that can be used as a basis for further.